Desenvolvimento de um oxímetro através de tecnologias IoT aplicado à dispositivos móveis - Anjos, Lucas Fernandes Alves dos (2020)
The health crisis caused by the corona virus (COVID-19) exposed the limitations of healthcare systems and created an alert for the need to use mobile technologies for medical monitoring. Besides being an important indicator for several medical activities, pulse oximetry is also considered essential in the monitoring of patients with COVID-19, being an indicator of the worsening of the disease. Although there are restrictions, it is important to consider the use of the Internet of Things (IoT) in the hospital environment, since this technology has revolutionized several sectors of the economy. Based on these facts the present work aims to develop a monitoring system for pulse oximetry and heart rate through the MAX30100 sensor and with the use of IoT technology for monitoring by mobile devices. Through the results of this work it was possible to state that the project is capable of sending vital sign data to a mobile device using IoT technologies.